Characterization of cytoplasmic polyadenylation element binding 2 protein expression and its RNA binding activity. Issue 5 (23rd December 2014) - Turimella, Sada Lakshmi; Bedner, Peter; Skubal, Magdalena; Vangoor, Vamshidhar Reddy; Kaczmarczyk, Lech; Karl, Kevin; Zoidl, Georg; Gieselmann, Volkmar; Seifert, Gerald; Steinhäuser, Christian; Kandel, Eric; Theis, Martin
ABSTRACT Cytoplasmic polyadenylation element binding (CPEB) proteins are translational regulators that are involved in the control of cellular senescence, synaptic plasticity, learning, and memory. We have previously found all four known CPEB family members to be transcribed in the mouse hippocampus. Aside from a brief description of CPEB2 in mouse brain, not much is known about its biological role. Hence, this study aims to investigate CPEB2 expression in mouse brain. With reverse transcription polymerase chain reaction (RT‐PCR) of total mouse brain cDNA, we identified four distinct CPEB2 splice variants. Single‐cell RT‐PCR showed that CPEB2 is predominantly expressed in neurons of the juvenile and adult brain and that individual cells express different sets of splice variants. Staining of brain slices with a custom‐made CPEB2 antibody revealed ubiquitous expression of the protein in many brain regions, including hippocampus, striatum, thalamus, cortex, and cerebellum. We also found differential expression of CPEB2 protein in excitatory, inhibitory, and dopaminergic neurons. In primary hippocampal cultures, the subcellular localization of CPEB2 in neurons and astrocytes resembled that of CPEB1. Electrophoretic mobility shift assay and RNA coimmunoprecipitation revealed CPEB2 interaction with β‐catenin and Ca2+/calmodulin‐dependent protein kinase II (both established CPEB1 targets), indicating an overlap in RNA binding specificity between CPEB1 and CPEB2. Furthermore, we identified ephrin receptor A4 as a putative novel target of CPEB2. In conclusion, our study identifies CPEB2 splice variants to be differentially expressed among individual cells and across cell types of the mouse hippocampus, and reveals overlapping binding specificity between CPEB2 and CPEB1. © 2014 Wiley Periodicals, Inc.